Study on Relative Abundance and Distribution of Tiger Prey Base (Ungulates) in Khata Corridor, Bardia National Park - Adhikari, Shalu; Khadka, Ambika (Kathmandu University Journal of Science Engineering and Technology, 2009)
The study provides information on distribution, abundance of wild ungulates and their link to habitat characteristics at a landscape level conservation. Khata Corridor is an important component of Terai Arc Landscape. It is about 9 km long and connects Bardia National Park, Nepal with Katarniaghat Wildlife Sanctuary, India. Relative abundance and distribution of Tiger prey base species (wild ungulates) was studied from mid April to mid June 2008 at Khata Corridor. A total of 127 transects (1 transect=625m, distance between adjacent transect=100m, distance between two parallel transect=100m) containing 2700 circular plots of 10m2 were laid and sampled following Smith et al (1999). A total of 2043 wild ungulates pellets were counted within the sampled area with a mean pellet group abundance of 0.75 pellets per plot. Mean pellet group abundance of Spotted deer, Wild boar, Monkey, Hog deer, Barking deer and Blue bull were 0.63, 0.06, 0.05, 0.02, 0.00 and 0.00 per plot respectively. Species wise ungulate abundance showed that Barking deer was highest in Low Density Mixed Forest, Spotted deer in Grassland, Hog deer in both Grassland and Low Density Mixed Forest, Blue bull only in Low Density Mixed Forest, Monkey in Riverine Forest and Wooded Grassland, and Wild boar in Wooded Grassland. Distribution pattern of wild ungulate species was of Clumped type (S2/a=93.10). Out of four habitat types, flood plains with riverine forest and grasslands were considered important habitats. Khata has been experiencing different levels of degradation also has tremendous conservation potential to ensure long term viability of large mammals (eg. Tigers) if restored and integrated into landscape level conservation plans.